Adolescents’ preferences of educational media on sugar sweetened beverages : A qualitative study - Faraji, Mahsa; Wiradnyani, Luh Ade Ari; Chandra, Dian Novita; Februhartanty, Judhiastuty; Fauzia, Khalida; Wangsa, Andrean; Widyahening, Indah Suci (Indonesian Nutrition Association, 2024)
Adolescents consume sugar-sweetened beverages (SSBs), their primary added sugar source, daily, yet there is a considerable SSBs’ knowledge, attitude, and practice (KAP) gap. Media literacy is crucial in enhancing student education and engagement through high-quality and digestible materials and methods. This study aims to identify the preferred educational media for SSBs among urban adolescents in Jakarta.